Real news about the news media and British politics - Newton, Kenneth 1940- (Cambridge University Press, 2024)
What role does the media play in British politics? There is growing concern that the media environment is biased, and that online news and social media spread fake news, conspiracy theories, propaganda, and foreign interference. Examining TV, radio, newspapers and the internet, Kenneth Newton unravels the real effects of the mainstream and alternative news media. With abundant evidence, Newton demonstrates that, contrary to popular belief: newspapers neither win nor lose elections; nor set election agendas; most citizens have a fairly mixed news diet and do not inhabit echo-chambers; social media influences on political attitudes are generally small and actually expand the range of news people get; impartial and reliable public service news still provides the bulk of the nation's news diet. Evidence shows that the main media effects on political attitudes and behaviour are positive and inform and mobilise citizens rather than influencing their voting choice
Title from publisher's bibliographic system (viewed on 09 Feb 2024)
Keywords: Press and politics / Great Britain / History / 21st century; Mass media / Political aspects / Great Britain / History / 21st century; Great Britain / Politics and government / 1945-